Antipathogenic Activity of Acroporid Bacterial Symbionts Against Brown Band Disease-Associated Bacteria - Rosa Amalia; Diah Ayuningrum; Agus Sabdono; Ocky Karna Radjasa (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2021)
The coral reefs’ condition in most regions in Indonesia has been declining due to coral diseases, such as Brown Band Disease (BrBD). A treatment for BrBD involves the use of biological control agents that have antagonistic properties against disease-causing agents. This study aimed to isolate bacteria from healthy hard coral, those associated with BrBD, and those that had bioactivities against BrBD. Sampling and identification of corals and BrBD were carried out in March 2015 at the Marine National Park of Karimunjawa. Bacteria from healthy and infected corals were isolated and purified. The isolates were subjected to antipathogenic assay using overlay and agar diffusion methods. Finally, molecular identification of active bacteria was carried out using the 16S rRNA gene amplification. As many as 57 bacterial isolates were obtained from healthy coral, as well as four bacterial isolates from coral with BrBD symptoms. A total of 15 bacterial isolates (26%) showed antipathogenic activity against BrBD-associated bacteria. Three isolates with the strongest antipathogenic activities, i.e., GAMSH 3, KASH 6, and TAPSH 1 were identified by 16S rRNA gene sequences. The results showed that they were aligned to Virgibacillus marismortui (97%), Oceanobacillus iheyensis (97%), and Bacillus cereus (96%), respectively.